A comparison of speaking up behavior during conflict with real and virtual humans. (November 2015) - Robb, Andrew; White, Casey; Cordar, Andrew; Wendling, Adam; Lampotang, Samsun; Lok, Benjamin
Highlights: Speaking up about errors is an important, yet difficult, preventative technique. We examined how nurses spoke up to a human and a virtual surgeon. Nurses behaved the same while speaking up to the human and virtual surgeon. Speaking up to a virtual human can be as difficult as speaking up to a real human. Learning to speak up to virtual humans may help people speak up in the real world. Abstract: Breakdowns in team communication are a common source of error. Unfortunately, even when errors are identified, team members may not speak up about the error, often out of fear of confrontation. We propose that virtual humans may be used to help prepare people to speak up. To this end, we conducted a between-subjects study examining speaking up behavior with real and virtual humans. Forty-eight nurses participated in a team training exercise that gave them an opportunity to speak up to a surgeon (either virtual or human, depending on condition) in order to protect a patient's safety. Our results suggest that speaking up behavior with the virtual surgeon closely approximated behavior with the human surgeon: no significant differences were found in participants' use of influence tactics ( p > 0.149 ) or in the outcomes obtained ( p = 0.788 ) . However, participants were significantly more likely to ask the virtual anesthesiologist for input when working with the human surgeon ( p < 0.05 ) . Our findings suggest that participants found speaking up to the real and virtual surgeon to be of comparable difficulty. This is an important prerequisite before virtual humans can be used to prepare people to speak up about errors.